Güncel Endodonti Çalışmaları V (Bahar) - Kuloğlu, Bircan; Doğan Çankaya, Tülin; Yüksel, Gizem; Tavşan, Oğuz; Başar, Özge; Şanal Çıkman, Ahter; İbiloğlu, Ayşe and Kiraz, Gülsen and Toker, Buse Cansu and Kaya Mumcu, Arzu and Çoban Öksüzer, Merve and Şanal Çıkman, Ahter and Kaşıkçı, Sena (Academician Publishing Book DOI Portal, 2024)
-